Long‐term outcome for kaposiform hemangioendothelioma: A report of two cases. Issue 2 (4th October 2016) - Schaefer, Beverly A.; Wang, Dehua; Merrow, Arnold C.; Dickie, Belinda H.; Adams, Denise M.
Abstract: Kaposiform hemangioendothelioma (KHE) is a rare aggressive vascular tumor of skin and deep soft tissues that typically presents in infancy and may be associated with a potentially life‐threatening coagulopathy known as Kasabach–Merrit phenomenon (KMP). Recent advances in medical therapy have successfully treated many patients. However, our knowledge regarding the natural history of these lesions and optimum surveillance strategies remains rudimentary. We report two young women who had KHE with KMP treated in infancy and presented in adolescence with comorbidities related to their KHE tumor. This presentation supports the need for long‐term surveillance in these patients.